Incentive schemes, private information and the double-edged role of competition for agents - Christina Bannier; Eberhard Feess; Natalie Packham; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
This paper examines the effect of imperfect labor market competition on the efficiency of compensation schemes in a setting with moral hazard and risk-averse agents, who have private information on their productivity. Two vertically differentiated firms compete for agents by offering contracts with fixed and variable payments. The superior firm employs both agent types in equilibrium, but the competitive pressure exerted by the inferior firm has a strong impact on contract design: For high degrees of vertical differentiation, i.e. low competition, low-ability agents are under-incentivized and exert too little effort. For high degrees of competition, high-ability agents are over-incentivized and bear too much risk. For a range of intermediate degrees of competition, however, agents' private information has no impact and both contracts are second-best. Interim efficiency of the least-cost separating allocation in the inferior firm is a sufficient condition for equilibrium existence. If this is violated, there can only be equilibria where the inferior firm ''overbids'', i.e. where it would not break even when attracting both agent types. Adding horizontal differentiation allows for pure-strategy equilibria even when there would be no equilibrium without overbidding in the pure vertical model, but equilibria with overbidding fail to exist.
Keywords: D82; D86; J31; J33; 330; incentive compensation; screening; imperfect labor market competition; vertical differentiation; horizontal differentiation; risk aversion